Implementation of Village Financial Management Through SISKEUDES in Pandanrejo Village - Ishlakhul Avita; Catur Wahyudi; Akbar Pandu Dwinugraha (Journal of Transformative Governance and Social Justice, 2023)
The use of digitalization in the implementation of village government is a necessity that needs to be realized. Moreover, in village financial management, the village financial system or Siskeudes is part of the digitization of village government administration. Unfortunately, its application in the village that is the pilot of the Batu city government's digitization project, namely Pandanrejo village, is still experiencing problems related to the system that is still running offline. This study aims to analyze and describe the implementation of village financial system management and its supporting and inhibiting factors. Descriptive qualitative is used in this type of research. The results of the study found that the implementation of village financial management through the application of siskeudes in Desa Pandanrejo was following the provisions which include planning, implementation, administration, reporting, and accountability.  However, there are some obstacles at some stages. The planning stage is constrained by the late delivery of the indicative ceiling from the City. There is an administration stage it is explained that this stage is the responsibility of the head of financial affairs, but because the HR of the head of financial affairs of Pandanrejo Village is low, this is the background for the delegation of authority to other staff to act as admins siskeudes.  Based on this, it is necessary to develop the human resources of village officials at the administrative level in the context of digital administration. Siskeudes needs to be fully supported by a network that can ensure that the system is always in online condition because the existing conditions in the application field are still offline. although this does not affect the performance of the village, it results in data not being quickly available and making it difficult for the Batu City Government